Understanding Adoption and Impacts of Conservation Agriculture in Eastern and Southern Africa: A Review - Ngoma, Hambulo; Angelsen, Arild; Jayne, Thomas S.; Chapoto, Antony (Frontiers in Agronomy, 2021)
Conservation Agriculture (CA) aims to concurrently promote agricultural productivity, local livelihoods, climate resilience and other environmental objectives. We review the emerging evidence base in Eastern and Southern Africa to address whether CA is climate smart and why adoption rates by smallholders remain generally very low. We first develop an adoption framework that can be used to assess when and where the different components of CA are expected to be adopted under different conditioning factors and consider options to make CA climate smart. Our results suggest that CA can contribute positively to productivity and adaptation/resilience objectives, although the degree of success varies considerably by farm, household regional characteristics. Overall, we find that capital-intensive (mechanized) CA is more likely to be adopted in areas of economic dynamism where capital is cheap relative to labor. Labor-intensive CA practices are more likely to be adopted in regions of economic stagnation where capital is expensive, and labor is abundant and cheap. A subnational focus is needed to identify economic conditions of different regions and agro-ecological zones and to test hypotheses derived from the framework in this paper and to propose the most appropriate CA packages for promotion. Our findings suggest that labor using variants of CA such as planting basins are more likely to be adopted than are capital using mechanized options in in (parts) of Malawi, Ethiopia, Kenya, Tanzania, Zambia and Zimbabwe. However, rising land scarcity (prices) and wages in the region present an opportunity for capital intensive, mechanized CA operations to be adopted if the cost of capital can be kept low and if there is a supportive environment for mechanization. We conclude that CA is climate smart and if adopted widely, it has the potential to help build resilience in smallholder farming systems. CA can be more climate smart, and its uptake can be enhanced by reframing, better targeting, adapting CA to location-specific economic and biophysical, and through greater and more effective public spending on research and development.